Ocean state - O'Nan, Stewart, 1961- (Atlantic Monthly Press, 2022)
"In the first line of Ocean State, we learn that a high school student was murdered, and we find out who did it. The story that unfolds from there with incredible momentum is thus one of the build-up to and fall-out from the murder, told through the alternating perspectives of the four women at its heart. Angel, the murderer, Carol, her mother, and Birdy, the victim, all come alive on the page as they converge in a climax both tragic and inevitable. Watching over it all is the retrospective testimony of Angel's younger sister Marie, who reflects on that doomed autumn of 2009 with all the wisdom of hindsight. Angel and Birdy love the same teenage boy, frantically and single mindedly, and are moved by the intensity of their feelings to extremes neither could have anticipated. O'Nan's expert hand paints a fully realized portrait of these women, but also weaves a compelling and heartbreaking story of working-class life in Ashaway, Rhode Island. Propulsive, haunting, and deeply rendered, Ocean State is a masterful novel by one of our greatest storytellers"--